0
$\begingroup$

I have the following sum that I would like to explore: $$d(S) = \sum_{n_1, n_2, \ldots, n_S = 0}^\infty \left( \left[\prod_{j=1}^S\frac{\alpha^{n_j}}{n_j!}\right]\sum_{k=1}^Nn_k^2\mu_k^2\right),$$

where $\alpha$ is a positive real number, $S$ is a positive integer, and

$$\mu_k = \xi\left(k - \frac{S+1}{2}\right).$$ I am using Mathematica to numerically find $d(S)$ for different values of $S$, which of course takes a long time (even for the truncated infinite sum). Is there some identity that I could make use of to simplify the summation in any way.

$\endgroup$
  • $\begingroup$ Does pulling the summation outside the product and takes its $S^{\mathrm{th}}$ power speed things up? (since it is independent of $j$) $\endgroup$ – Alex Vong Dec 13 '17 at 14:50
  • $\begingroup$ @AlexVong, thank you. This has been made clear in the notation $\endgroup$ – Sid Dec 13 '17 at 15:02
2
$\begingroup$

The way you wrote the round bracket was initially slightly ambiguous. I assume you mean the following $$ d(S) = \sum_{n_1, n_2, \ldots, n_S = 0}^\infty \left[\left(\prod_{j=1}^S\frac{\alpha^{n_j}}{n_j!}\right) \sum_{k=1}^Nn_k^2\mu_k^2\right]= \sum_{n_1=0}^\infty\frac{\alpha^{n_1}}{n_1!}\sum_{n_2=0}^\infty\frac{\alpha^{n_2}}{n_2!}\cdots \sum_{n_S=0}^\infty\frac{\alpha^{n_S}}{n_S!}\left(n_1^2\mu_1^2+\ldots +n_N^2\mu_N^2\right)\ . $$ If this is what you meant, and assuming $N\leq S$, then your sum is not that difficult. It is given by $$ d(S)=\sum_{n_1=0}^\infty\frac{\alpha^{n_1}}{n_1!}\sum_{n_2=0}^\infty\frac{\alpha^{n_2}}{n_2!}\cdots \sum_{n_S=0}^\infty\frac{\alpha^{n_S}}{n_S!}\left(n_1^2\mu_1^2+\ldots +n_N^2\mu_N^2\right)=\left[\sum_{n_1=0}^\infty\frac{\alpha^{n_1}}{n_1!}\sum_{n_2=0}^\infty\frac{\alpha^{n_2}}{n_2!}\cdots \sum_{n_S=0}^\infty\frac{\alpha^{n_S}}{n_S!}n_1^2\mu_1^2\right]+ $$ $$ +\left[\sum_{n_1=0}^\infty\frac{\alpha^{n_1}}{n_1!}\sum_{n_2=0}^\infty\frac{\alpha^{n_2}}{n_2!}\cdots \sum_{n_S=0}^\infty\frac{\alpha^{n_S}}{n_S!}n_2^2\mu_2^2\right]+\cdots+\left[\sum_{n_1=0}^\infty\frac{\alpha^{n_1}}{n_1!}\sum_{n_2=0}^\infty\frac{\alpha^{n_2}}{n_2!}\cdots \sum_{n_S=0}^\infty\frac{\alpha^{n_S}}{n_S!}n_N^2\mu_N^2\right]\ . $$ Hence $$ d(S)=\sum_{k=1}^N\underbrace{\sum_{n_1=0}^\infty\frac{\alpha^{n_1}}{n_1!}\cdots\sum_{n_{k-1}=0}^\infty\frac{\alpha^{n_{k-1}}}{n_{k-1}!}}_{(k-1)-terms}\sum_{n_k=0}^\infty\frac{\alpha^{n_k}}{n_k!}n_k^2\mu_k^2 \underbrace{\sum_{n_{k+1}=0}^\infty\frac{\alpha^{n_{k+1}}}{n_{k+1}!}\cdots\sum_{n_{S}=0}^\infty\frac{\alpha^{n_{S}}}{n_{S}!}}_{(S-k)-terms}\ . $$ All the sums except the $k$th give the same result $=e^\alpha$, while the $k$th sum gives $=e^{\alpha } \left(\alpha ^2+\alpha \right) \xi ^2 \left(k+\frac{1}{2} (-S-1)\right)^2$. Therefore the final result is $$ d(S)=\sum_{k=1}^N e^{\alpha (S-1)}e^{\alpha } \left(\alpha ^2+\alpha \right) \xi ^2 \left(k+\frac{1}{2} (-S-1)\right)^2=e^{\alpha S}\left(\alpha ^2+\alpha \right) \xi ^2 \frac{1}{12} \left(4 N^3-6 N^2 S+3 N S^2-N\right)\ . $$

$\endgroup$
  • $\begingroup$ sorry about the ambiguity - I have changed the question. Your first assumption is correct. How did you manage to rewrite $d(S)$ in that case? $\endgroup$ – Sid Dec 13 '17 at 15:18
  • $\begingroup$ uhm...I just distribute the product, $\sum_{n_1,n_2}f_1(n_1)f_2(n_2)=\sum_{n_1}f_1(n_1)\sum_{n_2}f_2(n_2)$... $\endgroup$ – Pierpaolo Vivo Dec 13 '17 at 15:20
  • $\begingroup$ To clarify, which of the two interpretations have you solved? $\endgroup$ – Sid Dec 13 '17 at 15:42
  • $\begingroup$ The first one. Which details are unclear? I can try to help more. $\endgroup$ – Pierpaolo Vivo Dec 13 '17 at 15:42
  • $\begingroup$ I don't follow how you managed to get the second line $\endgroup$ – Sid Dec 13 '17 at 15:45

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.